2017
DOI: 10.24843/10.24843/jchem.2017.v11.i02.p03
|View full text |Cite
|
Sign up to set email alerts
|

KANDUNGAN FORMALIN PADA IKAN BANDENG (Chanos chanos) DI PASAR TRADISIONAL DAN MODERN DI DENPASAR

Abstract: Telah dilakukan analisis kandungan formalin pada ikan bandeng di pasar tradisional dan modern di Denpasar. Ikan bandeng (Chanos chanos) diambil pada 4 lokasi yang berbeda dengan 2 lokasi di pasar tradisional dan 2 lokasi di pasar modern. Kandungan formalin dalam sampel dianalisis dengan alat spektrofotometri UV-Vis. Hasil analisis menunjukkan adanya kandungan formalin pada ikan bandeng. Konsentrasi formalin pada ikan bandeng sampel A dan B berturut-turut sebesar 15,16 ppm dan 13,44 ppm sedangkan pada sampel C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Some of the adverse effects of formalin if consumed regularly by the body include damage to the nervous system, kidneys, liver, and can cause asthma and cancer (Songur et al, 2010). Hardaningsih et al (2017) found the presence of formalin content in milkfish sold in traditional and modern markets in Denpasar. The same result was also reported by Lema and Jacob (2020) who found the addition of formalin to cob and mackerel at the Kupang City Market.…”
Section: Formalin and Boraxmentioning
confidence: 99%
“…Some of the adverse effects of formalin if consumed regularly by the body include damage to the nervous system, kidneys, liver, and can cause asthma and cancer (Songur et al, 2010). Hardaningsih et al (2017) found the presence of formalin content in milkfish sold in traditional and modern markets in Denpasar. The same result was also reported by Lema and Jacob (2020) who found the addition of formalin to cob and mackerel at the Kupang City Market.…”
Section: Formalin and Boraxmentioning
confidence: 99%
“…Timbal (terikat pada membran mitokondria dan bergabung dengan protein dan berperan dalam sintesis asam nukleat). (8) Sedimentasi merupakan salah satu proses yang terjadi disebabkan oleh alam dan artifisial manusia yang telah memberikan perubahan tatanan ekosistem, dimana sedimen tersebut diendapkan. Perpindahan logam berat yang terlarut dari badan air ke dalam sedimen akan terjadi apabila terdapat material organic pada permukaan sedimen yang akan mengikat logam tersebut.…”
Section: Pembahasanunclassified